(untitled) (Research, Society and Development, 2021)
Describe the etiology and resistance of bacterial isolates from blood cultures of patients admitted to the Intermediate Care Room of the University Hospital of Vale do São Francisco, Petrolina / PE. All blood cultures, performed by the Clinical Analysis Laboratory of the University Hospital, between January and December 2020 of patients admitted to the Intermediate Care Room through retrospective and quantitative analysis were retrospectively analyzed. The data were tabulated in Excel® spreadsheets and an analysis of absolute and percentage values was performed. The identification of bacteria and antibiograms were performed using the automated BD Phoenix ™ system, according to the methodology of the Clinical and Laboratory Standards Institute of 2020. 113 blood cultures were collected, 29 of which were positive (26%) for bacterial growth. The most prevalent bacteria were coagulase negative Staphylococcus (45%), Escherichia coli (17%) and Staphylococcus aureus (10%). Staphylococcus spp bacteria showed resistance to ampicillin and penicillin, while Klebsiella pneumoniae and Acinetobacter baumannii showed important resistance to carbapenems and cephalosporins. There was a predominance of gram-positive bacteria and 55% of the bacteria were Staphylococcus spp, all of which showed resistance to ampicillin and penicillin. In addition, there was resistance from K. pneumoniae and A. baumannii to carbapenems and cephalosporins. Through the study of the microbiological profile of bacteria related to nosocomial infections, it is possible to build adequate empirical antibiotic therapy protocols, as well as the design and implementation of preventive and control measures for these infections.